2020
DOI: 10.4103/aca.aca_140_19
|View full text |Cite
|
Sign up to set email alerts
|

Coronary cameral fistula and its complications: A case report

Abstract: Coronary cameral fistulas (CCFs) are rare arteriovenous malformations that may be congenital or acquired. The presentation of CCFs varies from asymptomatic in early age to symptomatic and start of complications upon aging. Although percutaneous closure with embolization can also be done, surgical closure of CCFs is a gold standard of treatment. We present the case of a 20-year-old patient with a fistula connecting right coronary artery and the right atrium, along with aortic valve endocarditis and congestive c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Rupture of an aneurysmal artery may result in thrombosis, infective endocarditis, and hemopericardium. Upadhyay et al reported a case of a 20-year-old female with a fistula between RCA and RA with aortic valve endocarditis and congestive cardiac failure 9 . In our case, the child was asymptomatic, the fistula was detected incidentally at 6 months of age by echocardiography.…”
Section: Discussionmentioning
confidence: 99%
“…Rupture of an aneurysmal artery may result in thrombosis, infective endocarditis, and hemopericardium. Upadhyay et al reported a case of a 20-year-old female with a fistula between RCA and RA with aortic valve endocarditis and congestive cardiac failure 9 . In our case, the child was asymptomatic, the fistula was detected incidentally at 6 months of age by echocardiography.…”
Section: Discussionmentioning
confidence: 99%
“…Whether ischemic symptoms occur is an important factor of complications after surgical intervention in CFS. The monitoring of intraoperative electrocardiography as well as transesophageal echocardiography can, to some extent, monitor the occurrence or absence of ischemia [Upadhyay 2020].…”
Section: Discussionmentioning
confidence: 99%